Analisis Routing Protocol Is-Is Dengan MPLS Traffic Engineering Menggunakan GNS3 - Hendra Bayu Susueno; Imam Tri Wibowo; Siti Ummi Masruroh; Dewi Khairani; I’im Umamil Khoiri (Fakultas Ilmu Komputer, 2021)
In the digital era is , the internet becomes a necessity . the increasing number of internet usage by various parties encourages ISPs to improve their service quality . To overcome the problem the IETF has introduced a service Multiprotcol . MPLS-TE allows for schemes TE where the tip router of the label switched path (LSP) can calculate the many routes efficiently through the network to the router tip of the tail of the LSP. TE consists of three steps principal that is the size , model, and control . MPLS-TE allows for schemes TE where the tip router of the label switched path (LSP) can calculate the many routes efficiently through the network to the router tip of the tail of the LSP. ISIS is one of the routing protocol that was created for the OSI mode, using the method of link state as a method of collecting the route , ISIS also will perform the collection of information and the status of all the links that exist in the network . Analysis of the IS-IS routing protocol with the Multiprotocol label switch Traffic Engineering based on the parameters of quality of service (QoS), namely throughput and packet loss where the simulation uses the GNS3 network emulator. The test results prove that the values of throughput and packet loss are not much different.